Implementation of Ministry of Agriculture Policy Number 64 of 2013 Concerning the Organic Agriculture System at the Food Security, Food Crops and Horticulture Office of North Sumatra Province - Hadian, Ahmad; Lubis, Zulkarnain; Hartono, Budi (Formosa Journal of Social Sciences (FJSS), 2024)
The implementation of the Regulation of the Minister of Agriculture Number 64 of 2013 concerning Organic Farming Systems is the focus of this study, with an emphasis on conditions in the Food Security, Food Crops, and Horticulture Office of North Sumatra Province. Through qualitative methods with primary data collection through interviews and secondary data from related sources, this study explores supporting and inhibiting factors in the implementation of these policies. The findings show that the implementation of this policy in the Food Security Office of North Sumatra Province has gone quite well. Community involvement, coordination between agencies, and effective utilization of resources have been carried out. The bureaucratic structure of the agency has facilitated the dissemination of this policy, while the attitude of the implementers indicates full compliance with the instructions of the central government